Diagnosis and treatment of invasive pulmonary aspergillosis in critically ill intensive care patients: executive summary of the German national guideline (AWMF 113-005) - Wichmann, Dominic; Hoenigl, Martin; Koehler, Philipp; Koenig, Christina; Lund, Frederike; Mang, Sebastian; Strauß, Richard; Weigand, Markus A.; Hohmann, Christian; Kurzai, Oliver; Heußel, Claus Peter; Kochanek, Matthias (Infection, 2025)
The executive summary of the guideline aims to provide the most relevant recommendations on the diagnosis and treatment of invasive pulmonary aspergillosis in critically ill patients in the intensive care unit.